English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i know how to do this but i am going blank on this problem:
rewrite so the y is a function of x.

3x + 2y - 4 = 2(5-y)


-im just confused about the two ys(and if you could explain the steps that would be nice)
please and thankyous

2007-10-21 08:30:38 · 4 answers · asked by Twilight182 4 in Science & Mathematics Mathematics

4 answers

3x + 2y - 4 = 10 - 2y
2y + 2y = 10 + 4 - 3x
4y = 14 - 3x
y = ( - 3 / 4 ) x + 14 / 4
y = ( - 3 / 4 ) x + 7 / 2

2007-10-25 07:44:09 · answer #1 · answered by Como 7 · 0 0

3x + 2y - 4 = 2(5-y)
3x = 10 - 2y - 2y + 4 expand 2(5-y), which equals 10 and -2y and brought 2y and -4 to the other side
3x = 14 - 4y simplify like terms
x = (14-4y)/3 isolate x by dividing both sides by 3

now substitute what x equals in for x in the equation and solve for y:
3 [(14-4y)/3] + 2y - 4 = 2(5-y)
14 - 4y +2y -4 = 10 - 2y multipy 3 into the brackets which cancels out the denominator.
-4y + 2y +2y = 10 - 14 + 4
0 = 0

2007-10-21 08:44:06 · answer #2 · answered by Anonymous · 0 0

3x + 2y - 4 = 2(5 - y)
3x + 2y - 4 = 10 - 2y
Add 2y to both sides of the equation.
3x + 4y - 4 = 10
4y = -3x + 14
Divide both sids by 4
y = (-3/4)*x + 7/2

2007-10-21 08:37:52 · answer #3 · answered by David D 2 · 0 0

just develop it and


3x+ 2y - 4 = 10 - 2y
3x+ 2y -4 + 2y = 10
3x + 2y+2y -4 = 10
3x +4 y - 4 =10
3x+ 4y= 10 + 4
3x + 4y = 14
4y = 14 - 3x
y = (-3x +14)/ 4
y = - 3x/4 + 7/2

2007-10-21 08:42:23 · answer #4 · answered by Alex_a 2 · 0 0

fedest.com, questions and answers